New directions in point-contact spectroscopy based on scanning tunneling microscopy techniques (Review Article) - Tartaglini, E.; Verhagen, T.G.A.; Galli, F.; Trouwborst, M.L.; Müller, R.; Shiota, T.; Aarts, J.; Ruitenbeek, J.M. van (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2013)
Igor Yanson showed 38 years ago for the first time a point-contact measurement where he probed the energy resolved spectroscopy of the electronic scattering inside the metal. Since this first measurement, the pointcontactspectroscopy (PCS) technique improved enormously. The application of the scanning probe microscopy (SPM) techniques in the late 1980s allowed achieving contacts with a diameter of a single atom. With the introductionof the mechanically controlled break junction technique, even spectroscopy on freely suspended chains of atoms could be performed. In this paper, we briefly review the current developments of PCS and show recent experiments in advanced scanning PCS based on SPM techniques. We describe some results obtained with both needle-anvil type of point contacts and scanning tunneling microscopy (STM). We also show our first attempt to lift up with a STM a chain of single gold atoms from a Au(110) surface.